2021
DOI: 10.1177/15248380211016016
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of the Career Choice of Helping Professionals Who Have Experienced Cumulative Harm as a Result of Adverse Childhood Experiences

Abstract: The pervasive effects of cumulative harm resulting from adverse childhood experiences influence all aspects of an individual’s life course. Research highlights a relationship between early trauma and career choice; however, there is a dearth of research pertaining specifically to cumulative harm and the influence on career choice in the helping professions. A systematic literature review was conducted to explore the associations of cumulative harm and childhood trauma on career decision making in people in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 77 publications
(237 reference statements)
3
22
0
Order By: Relevance
“…The majority of both the intrafamilial and institutional survivors engaged in prosocial behavior in later life, including general (informal) acts to benefit others, more structured (formal) acts (e.g., volunteering), and the choice of a social/caring profession (e.g., nursing). This is consistent with previous research in trauma populations, including childhood adversity survivors (Hernández-Wolfe, 2011 ; Bryce et al, 2021 ; Crann and Barata, 2021 ). Regarding the mechanisms linked to prosocial behavior, three themes were identified in both groups (i.e., enhanced empathy, self-identity, amelioration), as well as group-specific themes (i.e., compassion fatigue in intrafamilial survivors; denouncing detrimental social values in institutional survivors).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of both the intrafamilial and institutional survivors engaged in prosocial behavior in later life, including general (informal) acts to benefit others, more structured (formal) acts (e.g., volunteering), and the choice of a social/caring profession (e.g., nursing). This is consistent with previous research in trauma populations, including childhood adversity survivors (Hernández-Wolfe, 2011 ; Bryce et al, 2021 ; Crann and Barata, 2021 ). Regarding the mechanisms linked to prosocial behavior, three themes were identified in both groups (i.e., enhanced empathy, self-identity, amelioration), as well as group-specific themes (i.e., compassion fatigue in intrafamilial survivors; denouncing detrimental social values in institutional survivors).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the second theme, self-identity, participants reported a carer self-perception, which some linked to their choice of a social/caring profession in later life. This is in line with a recent systematic review on the career choice of helping professionals who experienced childhood adversities (Bryce et al, 2021 ). Evidence from 28 peer-reviewed studies identified several childhood adversity-related factors associated with a career choice in the helping professions, including family dysfunction, traits developed through the adversity, and parentification (i.e., children assuming the roles and responsibilities of a parent).…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, it is notable that significantly more students of the programs Social work, Teacher training and Arts had relatives with problematic substance use than had students of other study programs. A possible explanation is that a career choice in the helping professions, such as psychology, nursing, counseling, social work, human services and education, is known to be associated with family of origin dysfunction, parentification and childhood adversity (Bryce et al, 2021;Thomas, 2016). Especially in these study programs, it is important to be aware that students may have a family history of problematic substance use.…”
Section: Discussionmentioning
confidence: 99%
“…59)." Thus, a choice to pursue a career as a helping professional may be driven by the need to make meaning of early life adversity or trauma and the need to make that adversity matter by being of service to others who have experienced the same or similar adversities (Bryce et al, 2021). This developmental view of career construction might explain why the rates of ACEs among those who work in human service organizations are often higher than the general population.…”
Section: Early Life Adversity and Choosing A Career As A Helping Prof...mentioning
confidence: 99%
“…Direct service providers with lived experience of trauma and other adversities, especially experiences similar to the client populations they serve, have the potential to enhance service provision through deeper empathy (Bryce et al, 2021). However, it is important for individual providers and their organizations to be mindful of the heightened risk for burnout and stress.…”
Section: Implications For Practicementioning
confidence: 99%